Pengaruh Model Pembelajaran Role Playing Terhadap Hasil Belajar Bahasa Indonesia Siswa SDN Asemrowo II - Setyowati, Dwi; Kartikasari, Erlin; Nuryasana, Endang (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
The purpose of this study was to determine the effect of role playing learning models on student learning outcomes in Indonesian 8 Theme areas where I live in fiction stories grade 4 SDN Asemrowo II Surabaya. This research using is quantitative research using quasi experimental research designs. The sample used in this study is nonprability sampling with saturated sampling so that all student used as sample, all classes 4 consisting classes A and B. Class A was chosen as the control class dan class B was chosen as the experimental class, each class containing 25 student. The research instrument used was a test (pretest and posttest). The result of data analysis obtained from the independent t test are sig (2 tailed = 0,000) < É‘ 0, 05) it means that Ho is rejected dan HÉ‘ is accepted, Role Playing learing model influences student learning outcomes.